Analysis of superior commodities of capture fisheries sector at Kranji Village, Lamongan Regency - Dewi, Tri Ayu Rachma; Sawiji, Asri; Muslih, Toha (Journal of Marine Resources and Coastal Management, 2021)
The fisheries sector is one of the main driver of the national economy. One area of Indonesia that has fishery potential that can be developed is Paciran District, Lamongan Regency, East Java Province. This study was conducted in Kranji Village, which is located in Paciran District and has great pelagic fishery potential. The purpose of this study is to analyze the determination of superior fish commodities from the capture fisheries sector in Kranji Village. The determination of the leading commodities is carried out based on the LQ (Location Quotient) analysis method. The fluctuation of the catch in Kranji Village is affected by various aspects such as natural conditions, the number of fishing gear and government regulations. The fishing season in Kranji Village is divided into: (1) Tuna (Thunnus sp.) season which occurs from October to April with 15 to 20 trips per month; and (2) Goldstripe Sardinella (Sardinella gibbosa) season from May to September with 7 to 12 trips per month. Fishing gear in Kranji Village consists of purse sein, gill nets, cob nets, waring and mini trawlers. This study found that LQ value >1 for 12 fishes species: Bali Sardinella, Goldstripe Sardinella, Torpedo Scad, Longtail Tuna, Eastern Little Tun, Narrow-barred Spanish Mackerel, Giant Fish, Black Pomfret, Dorab Wolf Hearing, Orange-spotted Spinefoot (1.065), Other Fishes (1.057), and Short-bodied Mackerel (1.007). The results indicate that 12 fishes species have a comparative advantage and increasing income and contribution to the economy of Kranji Village.